2013
DOI: 10.1371/journal.pone.0074870
|View full text |Cite
|
Sign up to set email alerts
|

Effects of EZH2 Polymorphisms on Susceptibility to and Pathological Development of Hepatocellular Carcinoma

Abstract: BackgroundThe enhancer of zeste 2 (EZH2) gene encodes the histone methyltransferase that is the catalytic component of the polycomb repressive complex-2, which initiates epigenetic silencing of genes. The expression level of EZH2 in hepatocellular carcinoma (HCC) is highly correlated with tumor progression; however, it has not been determined if specific EZH2 genetic variants are associated with the risk of HCC. This study investigated the potential associations of EZH2 single-nucleotide polymorphisms with HCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 28 publications
0
23
0
2
Order By: Relevance
“…EZH2 is mutated in a variety of tumors including lymphomas and targeting of EZH2 protein with specific inhibitors show promising results in preclinical studies and early clinical trials [32–34]. Interestingly, it has been reported that EZH2 polymorphisms may contribute to susceptibility of tumor development and predict overall survival in some cancers [3538] and may have also contributed to progression of the disease in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…EZH2 is mutated in a variety of tumors including lymphomas and targeting of EZH2 protein with specific inhibitors show promising results in preclinical studies and early clinical trials [32–34]. Interestingly, it has been reported that EZH2 polymorphisms may contribute to susceptibility of tumor development and predict overall survival in some cancers [3538] and may have also contributed to progression of the disease in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…EZH2 regulates cell proliferation and differentiation by silencing polycomb group target genes, and has been linked to the aggressiveness of human cancers, including hepatocellular carcinoma [30]. Moreover, EZH2 promotes epithelial–mesenchymal transition, a process that is associated with both liver carcinogenesis and injury and repair process [31].…”
Section: Introductionmentioning
confidence: 99%
“…The C alleles of rs6950683 and rs3757441 may predict a higher risk of developing lymph-node metastasis in HCC [26]. In two independent studies, we found that the C/C genotype at rs3757441 was significantly associated with shorter progression free survival (PFS) and overall survival (OS) (p < 0.01 and p < 0.05, respectively) in metastatic colorectal cancer (mCRC) patients [32,33].…”
Section: Ezh2 Snvs Associated With Prognosis and Response To Therapymentioning
confidence: 96%
“…The most studied EZH2 SNVs to potentially predict cancer susceptibility are rs6950683 and rs3757441; carrying the risk T alleles of either rs6950683 or rs3757441 reduces the risk (Odd Ratio: 0.7) of developing oral squamous cell carcinoma susceptibility (OSCC) [24] and particularly small-cell lung cancer (SCLC), when compared to non-small-cell lung cancer patients [25]. Patients carrying the protective C allele at rs3757441 and rs6950683 also showed lower risk of developing hepatocellular carcinoma (HCC) and urothelial carcinomas (UCC), respectively [26,27]. At odds with these studies, the rs3757441 C allele was significantly associated with higher risk of developing ESCC and with higher advanced pathological staging in these tumors [28].…”
Section: Ezh2 Snvs Associated With Cancer Susceptibilitymentioning
confidence: 99%